Tuning the activity of cobalt 2-hydroxyphosphonoacetates-derived electrocatalysts for water splitting and oxygen reduction: insights into the local order by pair distribution function analysis - Vílchez-Cózar, Álvaro; Pérez-Colodrero, Rosario Mercedes; Bazaga-García, Montse; Marrero-López, David; El-Refaei, S.M.; Russo, Patricia A.; Pinna, Nicola; Olivera-Pastor, Pascual (Elsevier, 2023)
Pyrophosphate- or phosphide-based iron/cobalt electrocatalysts were prepared from the metal (R,S)−2-hydroxyphosphonoacetates to evaluate the effects of metal composition, N-doping and P-enrichment on the electrocatalytic activity. Rietveld and Pair Distribution Function analysis were used to determine phase composition. Irrespectively of the amorphous or crystalline nature, all pyrolyzed solids transformed under OER operation into biphasic Fe/CoO(OH), composed of discrete clusters (size ≤ 20 Å). Carbon paper-supported Fe0.2Co0.8O(OH) electrocatalysts displayed the best OER performances (overpotentials of 270–279 mV at 10 mA·cm−2), attributable to the formation of highly active bimetallic intermediate species. For HER, increased concentration of o-CoP in phosphide-based electrocatalysts resulted in improved performance, up to an overpotential of 140 mV. Employed as anode in alkaline water splitting, amorphous Fe-doped cobalt pyrophosphate and phosphide-derived electrocatalysts showed a cell voltage of 1.58 V at 10 mA·cm−2, with comparable stability to that of RuO2 and requiring lower voltage demand at high current densities.
Keywords: Catalizadores; Catálisis; Electroquímica; Cobalt phosphonates/pyrophosphates/phosphides; Electrocatalysts; PDF analysis; OER/HER/ORR; Water splitting